2005
DOI: 10.1200/jco.2005.05.531
|View full text |Cite
|
Sign up to set email alerts
|

ABL Mutations in Late Chronic Phase Chronic Myeloid Leukemia Patients With Up-Front Cytogenetic Resistance to Imatinib Are Associated With a Greater Likelihood of Progression to Blast Crisis and Shorter Survival: A Study by the GIMEMA Working Party on Chronic Myeloid Leukemia

Abstract: Our results show that, irrespective of the hematologic response, monitoring for emerging mutations in the first months of therapy may play a role in detecting patients with worse prognosis, for whom a revision of the therapeutic strategy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
233
1
14

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(263 citation statements)
references
References 37 publications
15
233
1
14
Order By: Relevance
“…23 The most common cause of secondary imatinib resistance is point mutations in BCR-ABL that prevent effective binding of imatinib but may retain kinase activity. [35][36][37][38][39] These mutations are clustered primarily within the kinase domain of BCR-ABL (ABL exons 4-10). 40 They exhibit differential relative resistance to imatinib in vitro.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…23 The most common cause of secondary imatinib resistance is point mutations in BCR-ABL that prevent effective binding of imatinib but may retain kinase activity. [35][36][37][38][39] These mutations are clustered primarily within the kinase domain of BCR-ABL (ABL exons 4-10). 40 They exhibit differential relative resistance to imatinib in vitro.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…According to this model, CML blast crisis would be expected to occur only in patients with an imatinib-resistant disease or in those developing resistance during treatment. Indeed, a recent study from the GIMEMA Working Party on CML reported that the early detection of BCR/ABL mutations in CML chronic phase patients is associated with a greater likelihood of disease progression (Soverini et al, 2005). Interestingly, a direct correlation also seems to exist between levels of BCR/ABL activity and development of imatinib resistance (Schultheis et al, 2005;Barnes et al, 2005a).…”
Section: CML Bcr/abl and Imatinibmentioning
confidence: 99%
“…For a relatively few CML patients, resistance to imatinib is present before, or develops during treatment. [8][9][10][11] Several strategies are available to treat imatinib-resistant patients, including imatinib dose escalation, dose adjustment based on pharmacokinetic assessments and the use of novel TKIs ( Figure 1, Table 1). …”
Section: Introductionmentioning
confidence: 99%